Financial Fraud Detection and the Importance of Internal Control - Amina, Zgarni (International Journal of Accounting and Financial Reporting, 2021)
In an environment that is becoming increasingly unstable due, primarily, to new international requirements and rapid changes, the problem of financial fraud detection has grown in importance. One of the main causes is the growing dependence on new technologies. This environment has required companies to adapt to face the new constraints. In fact, financial fraud is a problem that has a profound impact on the financial industry, government, businesses and ordinary consumers. The objective of this paper is double: the first one is to study the explanatory factors and the main variables developed in order to better detect the existence of financial fraud and we have emphasized the importance of taking into account non-accounting variables in the detection of financial fraud which remains little treated by empirical studies. The second objective of this research is to emphasize the importance of internal control, through a literature review, in the fight against financial fraud.